High Nuclear Expression of Yes-Associated Protein 1 Correlates With Metastasis in Patients With Breast Cancer - Cha, Yoon Jin; Bae, Soong June; Kim, Dooreh; Ahn, Sung Gwe; Jeong, Joon; Koo, Ja Seung; Yoo, Tae-Kyung; Park, Woo-Chan; Lee, Ahwon; Yoon, Chang Ik (Frontiers in Oncology, 2021)
Background: Yes-associated protein 1 (YAP1) is a transcription factor regulated by the Hippo pathway and functions as an oncogene in various solid tumors under dysregulated Hippo pathway. However, the role of YAP1 in breast cancer remains controversial. Here, we investigated the impact of different levels of nuclear YAP1 expression on the clinical characteristics and survival outcome in patients with breast cancer. Patients and Methods: Retrospectively obtained 455 breast tumor samples at Gangnam Severance Hospital were examined for YAP1 expression by immunohistochemistry, and the clinical data were analyzed. External validation was performed using a retrospective cohort and tissues in 482 patients from Severance Hospital. Results: High nuclear YAP1 expression was associated with hormone receptor negativity and aggressive tumor behavior, including lymph node metastasis, high Ki67 labeling index and inferior distant metastasis-free survival (DMFS, hazard ratio [HR] 2.271, 95% confidence intervals [CIs] 1.109-4.650, P=0.0249), and also confirmed inferior disease free survival (HR 3.208, 95% CIs 1.313-7.833, P=0.0105) in external validation cohort. In patients with triple-negative breast cancer (TNBC), high nuclear YAP1 expression was an independent significant determinant of poor DMFS (HR 2.384, 95% CIs 1.055-5.386, P=0.0367). Conclusion: Our findings suggest that nuclear YAP1 expression is a biomarker of adverse prognosis and a potential therapeutic target in patients with breast cancer, especially in TNBC.